DISTRIBUTED LOG ANALYSIS ON THE CLOUD USING MapReduce - Aydin, Galip; Hallac, Ibrahim R. (Univ Osijek, Tech Fac, 2016)
In this paper we describe our work on designing a web based, distributed data analysis system based on the popular MapReduce framework deployed on a small cloud; developed specifically for analyzing web server logs. The log analysis system consists of several cluster nodes, it splits the large log files on a distributed file system and quickly processes them using MapReduce programming model. The cluster is created using an open source cloud infrastructure, which allows us to easily expand the computational power by adding new nodes. This gives us the ability to automatically resize the cluster according to the data analysis requirements. We implemented MapReduce programs for basic log analysis needs like frequency analysis, error detection, busy hour detection etc. as well as more complex analyses which require running several jobs. The system can automatically identify and analyze several web server log types such as Apache, IIS, Squid etc. We use open source projects for creating the cloud infrastructure and running MapReduce jobs.
Distribuirana analiza zapisa na oblaku primjenom MapReduce
Keywords: cloud computing; Hadoop; log analysis; MapReduce